The Role Of A Notary In Preventing Money Laundering - I Made Pria Dharsana; Indrasari Kresnadjaja; I Putu Lingga Dhananjaya; Rizky Mustika Rini (Faculty of Law, Universitas Pekalongan, 2023)
The Notary's participation in preventing money laundering is to report to PPATK when they know of suspicious financial transactions related to the deed they made. The Notary's position as a whistleblower in the event of suspected suspicious financial transactions as an effort to prevent money laundering has not violated the principle of confidentiality of position. Instead, the Notary must apply the precautionary principle. Notary as the reporting party is an implementation of its obligations stipulated in Article 16 paragraph (1) point an of UUJN, namely acting trustfully and honestly. The State appoints notaries to serve the public in civil Law. Therefore Notaries must also take care not to let the State be harmed by attempts to disguise money from criminal acts. Notaries with this submit to higher interests. This is so that Notaries do not get involved in money laundering cases because they are considered to help carry out a criminal act